PELATIHAN PENYUSUNAN ANGGARAN PENJUALAN DAN PRODUKSI PADA DASA WISMA DAHLIA I TRUNUH DI KLATEN SELATAN: TRAINING ON SALES AND PRODUCTION BUDGET PREPARATION AT DASA WISMA DAHLIA I TRUNUH IN SOUTH KLATEN - Natalia Ratna Ningrum; Inayat Hanum Indriati; Guruh Ghifar Zalzalah; Fikri Farhan; Arif Sudaryana; Anindita Imam Basri (MESTAKA: Jurnal Pengabdian Kepada Masyarakat, 2023)
Budgeting is a crucial activity that must be undertaken by business practitioners. Without a well-established budgeting process and allocation, management would find it challenging to develop and achieve the company's goals in enhancing profitability. Therefore, this research aims to provide training related to the formulation of sales and production budgets. The method employed in this engagement is through providing training and lectures. Additionally, before receiving the training, participants in the engagement will undergo pre-tests and post-tests. Following this engagement activity, the managed businesses are expected to progress further and potentially increase the income of the women members of Dawis Dahlia I, as errors in sales and production estimates are minimized.